Step-by-step explanation:
To find the rule for the given mappings (1-4, 2-7, 3-10), observe the pattern in the numbers.
If we examine the mapping pairs:
1. 1-4
2. 2-7
3. 3-10
It appears that each input number (1, 2, 3) is multiplied by a certain factor and then has a constant value added to it to obtain the corresponding output.
In this case, the rule seems to be:
\[ \text{Output} = (\text{Input} \times 3) + 1 \]
You can verify this by applying the rule to each input:
1. \(1 \times 3 + 1 = 4\)
2. \(2 \times 3 + 1 = 7\)
3. \(3 \times 3 + 1 = 10\)
So, the rule for the given mappings is \( \text{Output} = (\text{Input} \times 3) + 1 \).